The Difference Levels of Hepcidin and Interleukin-6 between Obese and Non-Obese Type 2 Diabetes Mellitus - Mabruratussania Maherdika; Indranila Kustarini Samsuria; Meita Hendrianingtyas; Nyoman Suci Widyastiti; Muji Rahayu (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Inflammation occurs in chronic diseases such as type 2 diabetes mellitus (DM). Insulin resistance and inflammation in type 2 DM with obesity can increase interleukin (IL)-6, causing an increase in hepcidin synthesis in the liver. Increased inflammation can exacerbate the course of type 2 DM. This study aims to prove that there are differences in the levels of hepcidin and IL-6 between obese and non-obese type 2 DM.METHODS: This cross-sectional study was conducted on 61 patients with type 2 DM, consist of 22 male and 39 female with an age of more than 40 years. Type 2 DM subjects were obtained from a doctor's diagnosis and were divided into obese and non-obese groups based on body mass index (BMI). Hepcidin and IL-6 levels were examined using the Enzyme-Linked Immunosorbent Assay (ELISA) principle. The data were analyzed using an independent t-test and Mann-Whitney test.RESULTS: The mean level of hepcidin in the obese with type 2 DM group was 25.32±11.54 ng/mL, and non-obese was 11.94±5.31 ng/mL. The median level of IL-6 in the obese with type 2 DM group was 11.9 (5-61) pg/mL, and non-obese 4.8 (1.5-9.8) pg/mL. There was a significant difference in hepcidin and IL-6 levels between the obese and non-obese groups (p=0.000).CONCLUSION: Hepcidin and IL-6 levels in the obese group with type 2 DM were higher than non-obese group.KEYWORDS: type 2 diabetes mellitus, obesity, hepcidin, interleukin-6